Military Misfortunes : The Anatomy of Failure in War - Cohen, Eliot A. and Gooch, John (GHQ, Rawalpindi Services Book Club, 1995)
Rejecting accepted theories for unexpected military disasters, the authors brilliantly analyze disasters of great magnitude. They assert that military misfortune turns not on individual or collective failure but is rooted in the nature of the complex interconnections between men, systems, and organizations.
Include Notes and Index
Keywords: Military Art and Science -- History -- 20th Century -- Military History, Modern -- 20th Century -- Military Art and Science